A recombineering pipeline to clone large and complex genes in Chlamydomonas. Issue 4 (2nd February 2021) - Emrich-Mills, Tom Z; Yates, Gary; Barrett, James; Girr, Philipp; Grouneva, Irina; Lau, Chun Sing; Walker, Charlotte E; Kwok, Tsz Kam; Davey, John W; Johnson, Matthew P; Mackinder, Luke C M
Abstract: The ability to clone genes has greatly advanced cell and molecular biology research, enabling researchers to generate fluorescent protein fusions for localization and confirm genetic causation by mutant complementation. Most gene cloning is polymerase chain reaction (PCR)or DNA synthesis-dependent, which can become costly and technically challenging as genes increase in size, particularly if they contain complex regions. This has been a long-standing challenge for the Chlamydomonas reinhardtii research community, as this alga has a high percentage of genes containing complex sequence structures. Here we overcame these challenges by developing a recombineering pipeline for the rapid parallel cloning of genes from a Chlamydomonas bacterial artificial chromosome collection. To generate fluorescent protein fusions for localization, we applied the pipeline at both batch and high-throughput scales to 203 genes related to the Chlamydomonas CO2 concentrating mechanism (CCM), with an overall cloning success rate of 77%. Cloning success was independent of gene size and complexity, with cloned genes as large as 23 kb. Localization of a subset of CCM targets confirmed previous mass spectrometry data, identified new pyrenoid components, and enabled complementation of mutants. We provide vectors and detailed protocols to facilitate easy adoption of this technology, which we envision will open up new possibilities in algal and plant research. Abstract : A high-throughput system was developed to clone large, complex genes at high frequency and perform mutant complementation and protein tagging with a range of fluorophores in Chlamydomonas reinhardtii .